Training Using Rondo Style and Effect on Ball Possession in Soccer Players aged 12 – 14 years old in Talented sport centers - Asleawa, Wesam Najeeb; Ahmed, Faiza Abdel-Jabbar (Journal of Physical Education, 2022)
The research aimed at identifying the effect of Rondo training on ball possession in young soccer players aged 12 – 14 years old from national center for talented in soccer. The researchers used the experimental method on young soccer players from talented center. They conducted planning tests (ball possession) as well as many administration procedures. The program was applied in the international Shaab stadium and it lasted for three months. The results showed significant statistical differences in developing ball possession.